R. Wagner’s Der Ring des Nibelungen through the philosophical prism of Positive Psychotherapy - Maria Sergeeva (The Global Psychotherapist)
Using metaphors as an instrument of positive psychotherapy in some way reiterates the idea of the myths in Lévi-Strauss’ structuralism that natural phenomena are how myths seek to explain realities belonging to a logical order. Similarly, in their abstraction, metaphors strive to represent realities ‘clothed’ in words and cultural specifics. At the very same time, positive psychotherapy itself provides instruments for the analysis of these realities.